I. Seismic velocity heterogeneity in the crust and upper mantle under the Nevada Test Site. II. Source processes of great intraplate earthquakes. - Lynnes, Christopher Scott (1988)
I. Amplitudes of short-period teleseismic $P$ waves from underground explosions at the Nevada Test Site (NTS) exhibit coherent azimuthal variations that are positively correlated with travel time residuals. Both the Pahute Mesa and Yucca Flat subsites have similar patterns, indicating focusing and defocusing by deep ($>$400 km) heterogeneity. The differences between azimuthal patterns from these subsites are also coherent and positively correlated, indicating focusing-defocusing by near-source lateral velocity gradients. These variations are inverted via a thin lens procedure for warped velocity boundaries at depths of 25 and 160 km. Synthetic seismograms computed using the Kirchhoff integral show that these models explain much of the amplitude and some of the travel time behavior. Early $P$ coda from NTS tests also shows coherent azimuthal variations due to deep heterogeneity. Coda excitation varies systematically with source location within the Yucca Flat subsite, indicating contributions from near-source scattering. Inversion for isotropic point scatterers near the source suggests that topography may play a key role in scattering surface waves to teleseismic $P$ waves. II. The source-time functions of two great intraplate earthquakes, the 1975 North Atlantic (M$\sb{\rm w}$ = 7.8) and the 1977 Sumba (M$\sb{\rm w}$ = 8.3) events, are deconvolved from long-period $P$ waves. The 1975 earthquake changes focal mechanism from strike-slip to oblique normal, but no spatial variations of moment release can be resolved from the body waves. The normal-faulting 1977 Sumba earthquake has a central region with 9 m displacement, and 3 m displacement in surrounding regions. The rupture nucleated at 35 km depth near the edge of the high-displacement region and propagated 30 km west with little moment release before the main pulse, suggesting the rupture of an asperity. Discrepancies between the depth range and source duration implied by the $P$ waves (0-35 km and 40 s) and long-period surface waves (0-80 km and 80 s) can be ...